Dependence Analysis of the Solutions on the Parameters of Fractional Neutral Delay Differential Equations (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we discuss the dependence of the solutions on the parameters(order, initial function, right-hand function) of fractional neutral delay differentialequations (FNDDEs). The corresponding theoretical results are given respectively.Furthermore, we present some numerical results that support our theoretical analysis.